2019
DOI: 10.2478/qal-2019-0002
|View full text |Cite
|
Sign up to set email alerts
|

Implicit causality of action verbs at the interface between conceptual structure and discourse coherence relations

Abstract: Implicit causality of interpersonal transitive verbs (IC) pertains to preferences to attribute the cause of a given action to the subject or the object referent in active clauses. Causal attribution is operationalized as the probability of referential continuation in a subsequent explanatory clause. This paper presents an explorative investigation into the causal biases of action verbs, which in contrast to affective verbs have received less attention in IC research. We approach implicit causality as a discour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 63 publications
(98 reference statements)
0
13
0
Order By: Relevance
“…In so doing, earlier research has confirmed that L2 speakers depend on other cues which create the expectation for the subject re-mention, especially for familiar subject, parallel function preferences and first-mention (Quyen, 2017). Accordingly, L2 learners have been confirmed to be sensitive to verb-bias and as such, depend on this information in referential process for second languages (Kuehnast, & Meier, 2019).…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…In so doing, earlier research has confirmed that L2 speakers depend on other cues which create the expectation for the subject re-mention, especially for familiar subject, parallel function preferences and first-mention (Quyen, 2017). Accordingly, L2 learners have been confirmed to be sensitive to verb-bias and as such, depend on this information in referential process for second languages (Kuehnast, & Meier, 2019).…”
Section: Introductionmentioning
confidence: 87%
“…Studies have shown that pronoun determination is not merely limited to morphosyantacticconstrictionsincluding number, sexual category and individual, but equally soft limitations including the first-mention predilection, subject preference, grammatical parallelism and, finally, Implicit Causality Bias (Kuehnast, & Meier, 2019). IC bias refers to the bias, as indicated by interpersonal verbs, about the time proportions their object and subject arguments get re-mentioned in a specific sample of clarifications for the possibility described by the verb (Cheng &Almor, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations